Guerrilla travel tactics : hundreds of simple strategies guaranteed to save road warriors time and money - Levinson, Jay Conrad (AMACOM, 2004)
Annotation Entrepreneurs and professionals are often neglected by travel suppliers when it comes to favourable pricing. Guerilla Travel Tactics presents independent business travellers with a clear, step-by-step plan for saving time and money when travelling at their own expense. The upbeat approach of Guerilla Travel Tactics will instill confidence in the business traveller to conquer soaring travel costs. Packed with inside information, the book contains topics such as getting the lowest possible air fares, finding hidden discounts at hotels, using the internet and credit cards to save money and buying only the travel insurance that is needed.